Institutions and Financial Inclusion in Rural Uganda: the Mediating Role of Social Capital - Okello Candiya Bongomin, George; Ntayi, Joseph M.; Munene, John C.; Akol Malinga, Charles (Journal of African Business, 2018)
The study examined the mediating role of social capital in the relationship between institutions and financial inclusion of poor households in rural Uganda. Cross-sectional design was adopted and data were collected and analyzed using SPSS/20, MedGraph and Sobel-z test. The findings indicated that social capital partially mediates the relationship between institutions and financial inclusion. Besides, institutions and financial inclusion are significantly related. Thus, managers of financial institutions, financial inclusion working groups, and policy makers should pay more attention to the role of social capital in promoting cooperative behavior among the poor in accessing scarce resources such as financial services.
Keywords: Social capital; Institutional pillars; Rural poor; Financial inclusion; Uganda